Atmospheric responses to oceanic eddies in the Kuroshio Extension region. Issue 13 (6th July 2015) - Ma, Jing; Xu, Haiming; Dong, Changming; Lin, Pengfei; Liu, Yu
Abstract We examined atmospheric responses to 35, 000+ oceanic eddies in the Kuroshio Extension region during the period of 2006–2009. Using satellite data, we showed that cold (warm) eddies cause surface winds to decelerate (accelerate) and reduce (increase) latent and sensible heat fluxes, cloud liquid water, water vapor content, and rain rate; all of these changes are quantified. Both the linear correlation between wind divergence and downwind sea surface temperature (SST) gradient and the correspondence between vorticity and crosswind SST gradient support the vertical momentum mixing mechanism, which indicates that SST perturbations modify surface winds by changing the vertical turbulent mixing in the marine atmospheric boundary layer (MABL). High‐resolution National Centers for Environmental Prediction Climate Forecast System Reanalysis (CFSR) data can reproduce the atmospheric responses to the oceanic eddies in the MABL albeit with some differences in intensity. In addition, the CFSR data reveal that the atmospheric responses to these oceanic eddies are not confined in the MABL. MABL deepens (shoals) over the warm (cold) eddies; enhanced (reduced) vertical transport of transient zonal momentum occurs over the warm (cold) eddies from the sea surface to about 850 hPa level; vertical velocity anomalies over oceanic eddies penetrate beyond the MABL into free atmosphere; there exists a positive correlated relationship between SST and convective rain rate anomalies, indicative of ocean eddies' impact on the free troposphere. However, the composites of cloud liquid water and rain rate are different from the results based on the satellite data.